UJI KELAYAKAN MODUL BERBASIS SELF HELP BOOK TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII SMPN 1 CIRACAP - Sa'diah, Humaeroh; Eti Rohaeti, Euis; Rezza Septian, Muhammad (IKIP Siliwangi, 2024)
The purpose of this study was to determine the results of the validation of the feasibility of the self-help book-based module on learning motivation. Technical analysis of data using Microsoft Excel which is then analyzed descriptively. Instruments in the self-help book-based module validation assessment include the suitability of the material, the suitability of the design, instructions for use of the self-help book-based module and the benefits of the self-help book-based module to students. The results showed that the results of the self-help book-based module feasibility test conducted by 3 validators stated that the self-help book-based module was in the